2018
DOI: 10.1007/978-3-319-79090-9_10
|View full text |Cite
|
Sign up to set email alerts
|

Secure Data Processing in the Cloud

Abstract: Data protection is a key issue in the adoption of cloud services. The project "RestAssured-Secure Data Processing in the Cloud," financed by the European Union's Horizon 2020 research and innovation programme, addresses the challenge of data protection in the cloud with a combination of innovative security solutions, data lifecycle management techniques, run-time adaptation, and automated risk management. This paper gives an overview about the project's goals and current status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…• A general, easy-to-use and enforceable data protection approach suitable for large-scale commercial processing 7 • Maintaining robust data privacy with utility guarantees, also implying the need for state-of-the-art data analytics to cope with encrypted or anonymised data 8,9 • Risk-based approaches calibrating data controllers' obligations regarding privacy and personal data protection 10 • Combining different techniques for end-to-end data protection (Mann et al 2018;Stojmenovic et al 2016) The last point has also been observed by the E-SIDES project, who have investigated a wide range of technologies for privacy preservation in big data: "In practice, the technologies need to be combined to be effective and there is no single most important class of technologies". 11 Another challenge when designing privacy solutions for big data is the number of data sources, which can result in different settings where stakeholders can have varying degrees of access to the processed data.…”
Section: Challenges To Security and Privacy In Big Datamentioning
confidence: 99%
“…• A general, easy-to-use and enforceable data protection approach suitable for large-scale commercial processing 7 • Maintaining robust data privacy with utility guarantees, also implying the need for state-of-the-art data analytics to cope with encrypted or anonymised data 8,9 • Risk-based approaches calibrating data controllers' obligations regarding privacy and personal data protection 10 • Combining different techniques for end-to-end data protection (Mann et al 2018;Stojmenovic et al 2016) The last point has also been observed by the E-SIDES project, who have investigated a wide range of technologies for privacy preservation in big data: "In practice, the technologies need to be combined to be effective and there is no single most important class of technologies". 11 Another challenge when designing privacy solutions for big data is the number of data sources, which can result in different settings where stakeholders can have varying degrees of access to the processed data.…”
Section: Challenges To Security and Privacy In Big Datamentioning
confidence: 99%